Կասպից ծովի գազի արտահանման խնդիրը Թուրքիա-Վրաստան-Ադրբեջան համագործակցության համատեքստում - Դավթյան, Էրիկ (YSU Journal of International Affairs, 2017)
The article analyzes the Turkey-GeorgiaAzerbaijan energy cooperation under the framework of the Baku-Tbilisi-Erzurum gas pipeline and its importance for each of the three states. In this regard, the research discusses the Trans-Caspian gas pipeline project, related problems and perspectives for the trilateral cooperation. It also assesses the influence of the EU and U.S. on the TurkeyGeorgia-Azerbaijan trilateral energy cooperation.
Keywords: Turkey, Georgia, Azerbaijan, South Caucasus, Baku-Tbilisi-Erzurum gas pipeline, Trans-Caspain gas pipeline, Southern Gas Corridor